2013
DOI: 10.1039/c3nr02907g
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic properties of graphene thin films deposited by a Langmuir–Blodgett assembly

Abstract: Large area thin films of few-layered unfunctionalized graphene platelets are developed with fine control over the thickness. The thin films are obtained by a Langmuir-Blodgett assembly at the interface of graphene solution in N-methyl-2-pyrrolidone (NMP) and water, and their optoelectronic properties and conduction mechanism are investigated in relation to lateral flake size and thin film thickness. The electrical conductivity and carrier mobility are affected by the flake size (200 nm to 1 μm) and by the pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 83 publications
2
46
0
Order By: Relevance
“…Moreover, the possibility of having a large class of solution‐processed 2D materials enables their integration with polymeric materials or deposition/coating on different substrates. In this context, progress on large‐scale placement of 2D materials–based inks by the various deposition/coating techniques such as Langmuir–Blodgett, spin‐, spray‐ and rod‐coating, and inkjet printing, is enabling printing of 2D materials–based films and heterostructures on a large scale . Nonetheless, apart from the uniformity of large‐area films, the roughness of the deposited film is still an issue for both optical and electronic properties of the deposited films and worse than those obtained by micromechanical cleavage or the direct growth.…”
Section: D Materials: Production and Processingmentioning
confidence: 99%
“…Moreover, the possibility of having a large class of solution‐processed 2D materials enables their integration with polymeric materials or deposition/coating on different substrates. In this context, progress on large‐scale placement of 2D materials–based inks by the various deposition/coating techniques such as Langmuir–Blodgett, spin‐, spray‐ and rod‐coating, and inkjet printing, is enabling printing of 2D materials–based films and heterostructures on a large scale . Nonetheless, apart from the uniformity of large‐area films, the roughness of the deposited film is still an issue for both optical and electronic properties of the deposited films and worse than those obtained by micromechanical cleavage or the direct growth.…”
Section: D Materials: Production and Processingmentioning
confidence: 99%
“…Hitherto, exfoliated graphene[64b,68,160] and BP have been organized into LB films. Kim et al[160a] reported on the formation of LB films from graphene/NMP dispersion.…”
Section: Patterning Of 2d Inks Into Functional Structures For Electromentioning
confidence: 99%
“…On the one hand, liquidphase exfoliation of graphite into graphene is emerging as a suitable up-scalable method for the production of high quality graphene. [5][6][7][8][9] On the other hand, different strategies have been proposed in order to open a band gap in graphene such as the production of reduced graphene oxide 10,11 or graphene nanoribbons. [12][13][14][15][16] A different way of employing graphene for electronics relies on the use of hybrid solutions that combine graphene with suitable molecules to enable reciprocal modification of the component properties, e.g.…”
mentioning
confidence: 99%